Green Husk of Walnuts (Juglans regia L.) from Southern Italy as a Valuable Source for the Recovery of Glucans and Pectins - Chiara La Torre; Paolino Caputo; Pierluigi Plastina; Erika Cione; Alessia Fazio (Fermentation, 2021)
Walnut green husk is an agricultural waste produced during the walnut (Juglans regia L.) harvest, that could be valued as a source of high-value compounds. In this respect, walnut green husks from two areas of Southern Italy (Montalto Uffugo and Zumpano), with different soil conditions, were investigated. Glucans and pectins were isolated from dry walnut husks by carrying out alkaline and acidic extractions, respectively, and then they were characterized by FT-IR, scanning electron microscopy (SEM) and differential scanning calorimetry (DSC). The colorimetric method for the enzymatic measurement of α- and β-glucans was performed. The maximum total glucan yield was recovered from Montalto walnut husks (4.6 ± 0.2 g/100 g DM) with a β-glucan percentage (6.3 ± 0.4) higher than that calculated for Zumpano walnut husks (3.6 ± 0.5). Thermal analysis (DSC) confirmed the higher degree of crystallinity of glucans from Zumpano. The pectin content for Montalto husks was found to be 2.6 times that of Zumpano husks, and the esterification degree was more than 65%. The results suggested that J. regia L. green husks could be a source of glucans and pectins, whose content and morphological and thermal characteristics were influenced by different soil and climate conditions.